2020
DOI: 10.1016/j.isci.2020.101533
|View full text |Cite
|
Sign up to set email alerts
|

Single-Chain Lanthanide Luminescence Biosensors for Cell-Based Imaging and Screening of Protein-Protein Interactions

Abstract: Summary Lanthanide-based, Förster resonance energy transfer (LRET) biosensors enabled sensitive, time-gated luminescence (TGL) imaging or multiwell plate analysis of protein-protein interactions (PPIs) in living cells. We prepared stable cell lines that expressed polypeptides composed of an alpha helical linker flanked by a Tb(III) complex-binding domain, GFP, and two interacting domains at each terminus. The PPIs examined included those between FKBP12 and the rapamycin-binding domain of m-Tor (FRB)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Surprisingly, first experiments using the exact same sample preparation conditions as for CW FRET did not result in any Tb PL. Because Tb is very stable in various buffers (including TBS) and has been applied to many in-solution assays and for live cell and in vivo imaging without significant PL quenching, 20,[35][36][37][38] we assumed that the fixation procedure combined with incubation of the fixed cells with an aqueous buffer (i.e., the TBS buffer washed out some of the PFA fixative) caused the Tb PL quenching. We found that removal of TBS from the cells (i.e., without addition of fresh TBS after the three usual washing steps) and direct imaging resulted in bright PL signals ( ) demonstrated that the detection channels were specific to their probes and that FRET could only be detected when both probes were present.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, first experiments using the exact same sample preparation conditions as for CW FRET did not result in any Tb PL. Because Tb is very stable in various buffers (including TBS) and has been applied to many in-solution assays and for live cell and in vivo imaging without significant PL quenching, 20,[35][36][37][38] we assumed that the fixation procedure combined with incubation of the fixed cells with an aqueous buffer (i.e., the TBS buffer washed out some of the PFA fixative) caused the Tb PL quenching. We found that removal of TBS from the cells (i.e., without addition of fresh TBS after the three usual washing steps) and direct imaging resulted in bright PL signals ( ) demonstrated that the detection channels were specific to their probes and that FRET could only be detected when both probes were present.…”
Section: Resultsmentioning
confidence: 99%
“…The improved signal-tobackground ratios of TG and TG-FRET imaging (compared to CW imaging) underline the significant benefits that lanthanide complexes can bring to advanced high-contrast PL imaging. 9,34,37,[41][42][43][44][45][46] Notably, lanthanide-based TG PL imaging of fixed cells or tissues is not common and considering that the well-established solution-phase TG-FRET assays have only recently been implemented into advanced live cell and in vivo imaging, we can anticipate that the same performance can be expected for carefully optimized TG imaging on fixed cells. Similar to immunohistochemistry, the performance of in situ PLA depends on the fixation and pretreatment conditions, the applied antibody-DNA probes, and the careful adaption of assay components and their concentrations, which are important optimization steps that are beyond our in situ RCA-FRET proof-of-concept study.…”
Section: Discussionmentioning
confidence: 99%
“…This major problem can be addressed by lanthanide-based resonance energy transfer (LRET), where a time-gate delay of 10–100 μs is employed between probe excitation and signal acquisition to eliminate ns-long background fluorescence signal. Indeed, rapid development of this emerging method has been observed in recent years, as luminescent complexes of lanthanide cations (Tb 3+ and Eu 3+ , in particular) have been employed as donor chromophores to fluorescent proteins [ 35 , 36 , 37 ]. In light of this, the binding of Tb 3+ could be, in principle, employed to identify SPL2 ubiquitination substrates and E2s in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used Rac1 as a model system to elaborate on our recently reported biosensor design that incorporates rigid, helical linker domains and luminescent terbium (Tb(III)) complexes as energy transfer donors 20 , 21 . Our objectives were two-fold: (i) to develop LRET-type biosensors with ER/K linkers for multi-well plate TGL assays of Rac1 inhibition; and (ii) to evaluate the effects of ER/K linkers on the dynamic range of FRET-type Rac1 biosensors.…”
Section: Introductionmentioning
confidence: 99%